VIOLENCE AGAINST CHILDREN IN THE CYBERSPACE: A NEW CHALLENGE TO ISLAMIC LAW - Wahyu Aji Pratama; M. Saeful Amri; Abdul Rahim Hakimi (Program Studi Hukum Keluarga dan Hukum Ekonomi Syariah, Program Pascasarjana Institut Agama Islam Negeri (IAIN) Ternate, 2025)
This study examines the application of maqāṣid al-syarī'ah in the framework of national cyber regulations, especially related to child protection in the digital space. Using a normative qualitative approach, this study analyzes relevant laws and regulations, classical and contemporary maqāṣid literature, and recent studies on forms of digital crimes against children. The results show that the digital ecosystem presents various multidimensional threats to the protection of reason (ḥifẓ al-'aql), heredity (ḥifẓ al-nasl), and property (ḥifẓ al-māl), so an integrative framework is needed that bridges the goals of Islamic law with modern cyber governance. This study found that there is a value gap in Indonesia's cyber regulatory structure, especially the absence of a maqāṣid-based ethical paradigm in digital child protection arrangements. The novelty of this research lies in the formulation of a new conceptual integration model between maqāṣid al-syarī'ah and national cyber regulations for child protection. This integrative model has never been proposed in previous research and provides a conceptual basis for the development of ta'zīr-based digital governance policy guidelines and governance in the future.